Incorporation of inorganic mercury (Hg2+) in pelagic food webs of ultraoligotrophic and oligotrophic lakes: The role of different plankton size fractions and species assemblages - Soto Cárdenas, Estela Carolina (2014)
In lake food webs, pelagic basal organisms such as bacteria and phytoplankton incorporate mercury (Hg2+) from the dissolved phase and pass the adsorbed and internalized Hg to higher trophic levels. This experimental investigation addresses the incorporation of dissolved Hg2+ by four plankton fractions (picoplankton: 0.2–2.7 μm; pico + nanoplankton: 0.2–20 μm; microplankton: 20–50 μm; and mesoplankton: 50–200 μm) obtained from four Andean Patagonian lakes, using the radioisotope 197Hg2+. Species composition and abundance were determined in each plankton fraction. In addition, morphometric parameters such as surface and biovolume were calculated using standard geometric models. The incorporation of Hg2+ in each plankton fraction was analyzed through three concentration factors: BCF (bioconcentration factor) as a function of cell or individual abundance, SCF (surface concentration factor) and VCF (volume concentration factor) as functions of individual exposed surface and biovolume, respectively. Overall, this investigation showed that through adsorption and internalization, pico + nanoplankton play a central role leading the incorporation of Hg2+ in pelagic food webs of Andean lakes. Larger planktonic organisms included in the micro- and mesoplankton fractions incorporate Hg2+ by surface adsorption, although at a lesser extent. Mixotrophic bacterivorous organisms dominate the different plankton fractions of the lakes connecting trophic levels through microbial loops (e.g., bacteria–nanoflagellates–crustaceans; bacteria–ciliates–crustaceans; endosymbiotic algae–ciliates). These bacterivorous organisms, which incorporate Hg from the dissolved phase and through their prey, appear to explain the high incorporation of Hg2 + observed in all the plankton fractions.